Lean for systems engineering with lean enablers for systems engineering - Oppenheim, Bohdan W., 1948- (Wiley, 2011)
"The book describes the cutting-edge field of Lean for Systems Engineering and the new intellectual product Lean Enablers for Systems Engineering, LEfSE, a comprehensive checklist of 194 practices of Systems Engineering, focused on creating value without waste in large technological programs."--